Assessment of heavy metals in water, sediment, Anabas testudineus and Eichhornia crassipes in a former mining pond in Perak, Malaysia. Issue 7 (9th August 2017) - Kamari, Azlan; Yusof, Norjan; Abdullah, Hanisom; Haraguchi, Akira; Abas, Mohd Fahami
ABSTRACT: The concentrations of Al, As, Cd, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Sn and Zn were analysed in water, sediment, muscle of climbing perch fish ( Anabas testudineus ), and tissue of water hyacinth plants ( Eichhornia crassipes ) collected from a former tin-mining pond in Perak, Malaysia. The monitoring was performed during the minimum and maximum rainfall periods. The concentrations of As, Cr, Fe, Ni, Pb and Zn in water exceeded the permissible limits set by the Interim National Water Quality Standards for Malaysia (INWQS). The risk index (RI) values determined for As, Cd, Cr, Cu, Hg, Pb and Zn in sediment presented a low degree of ecological risk. The order of the top three heavy metals measured in fish muscle was Zn > Fe > Al. The estimated daily intake (EDI) of As and Cr exceeded the allowable limits in both rainfall periods. The bioconcentration factor (BCF) and translocation factor (TF) values of Zn in water hyacinth were 24.865 and 3.214, respectively. The concentrations of Cu and Zn in the plant tissue were significantly correlated ( p < .05) with the concentrations of heavy metals in water. Overall, climbing perch and water hyacinth are excellent bioindicators of environmental impacts on water bodies.